Survey and morpho-molecular characterization of the bhendi powdery mildew incited by Golovinomyces cichoracearum (DC.) V.P. Heluta - Lokesh, R; Sundaramoorthy, S; Ajaydesouza, V P; Mule, H R; Sathiya, A V (Plant Science Today, 2025)
Abelmoschus esculentus L. (bhendi), commonly referred to as okra, is a significant vegetable crop extensively cultivated in India due to its high nutritional value and economic importance. It serves as an abundant source of vitamins, minerals and dietary fibre, establishing itself as a fundamental component in numerous Indian households. However, it is attacked by numerous biotic and abiotic factors, among which powdery mildew causes severe yield loss. Roving survey undertaken across key bhendi-growing regions of Tamil Nadu exposed that incidence of powdery mildew, expressed as Percent Disease Index (PDI), ranged from 22.37 % to 74.57 %. The top three villages with the PDI were Kannivadi in Dindigul district with 74.57 %, followed by Kollapatti in Dindigul district with 71.85 % and Neikarapatti in Dindigul district with 65.35 %. The village with the least disease incidence was Gengaveli in Attur, Salem district, with 22.37 %. Pathogenicity assays performed with fifteen Golovinomyces sp. isolates led to the manifestation of characteristic powdery mildew symptoms. Morphological studies of all fifteen isolates were performed using a stereo binocular microscope and a scanning electron microscope (SEM). The most virulent isolate, AUGC02, which exhibited the highest disease incidence, was molecularly characterized using ITS universal fungal primers and confirmed as G. cichoracearum (GenBank Accession: PP373832), providing valuable insights for disease management strategies.